Laser trimming of graphene oxide for functional photonic applications. (23rd January 2017) - Zheng, Xiaorui; Lin, Han; Yang, Tieshan; Jia, Baohua
Abstract: This article reviews the recent photonic applications on graphene oxide and reduced graphene oxide films via the direct laser printing method. Attention has been paid to the unique optical property modulations of graphene oxide films during the laser reduction process, which enable a wide range of functional photonic and optoelectronic devices. The exotic properties of graphene oxide during the laser reduction process, including the tunable dispersion relation, flexible patterning capability, surface functionalization possibility, wavefront shaping ability, and the mechanical robustness and strength, make it a promising integratable platform for the next-generation ultrathin, light-weight and flexible photonic and optoelectronic applications.